2021
DOI: 10.1016/j.jid.2020.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Injection of Muse Cells as a Potential Therapeutic Approach for Epidermolysis Bullosa

Abstract: 2020). ACE2 expression is more widely distributed than that of B 0 AT1 (Yan et al., 2020), which may explain why some of the ACE2 expressing organs, such as lung and heart, are attacked by SARS-CoV-2, whereas others are not.Apart from ACE2, there may be another way for SARS-CoV-2 to infect host cells. ACE2 is scarcely present in immune cells. However, most patients with severe acute respiratory syndrome and patients with COVID-19 have lymphopenia; some patients may even have spleen and lymph nodes necrosis (Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…They are normally located in the bone marrow, peripheral blood, and connective tissues of organs and are thus non-tumorigenic 10 13 . Muse cells are unique for several reasons: they recognize damaged tissue and selectively accumulate at the site of damage by intravenous injection because they express sphingosine-1-phosphate (S1P) receptor 2, which recognizes the S1P produced by damaged/apoptotic cells; after homing to the damaged site, Muse cells replace damaged/apoptotic cells by spontaneous differentiation into the damaged/apoptotic cell-type, and contribute to tissue repair, as shown by animal models of stroke, acute myocardial infarction, epidermolysis bullosa, chronic kidney disease and liver cirrhosis 14 18 . Besides their effects on tissue repair, Muse cells have pleiotropic effects including neovascularization, immunomodulation, trophic-, anti-apoptotic-, and anti-fibrotic effects 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…They are normally located in the bone marrow, peripheral blood, and connective tissues of organs and are thus non-tumorigenic 10 13 . Muse cells are unique for several reasons: they recognize damaged tissue and selectively accumulate at the site of damage by intravenous injection because they express sphingosine-1-phosphate (S1P) receptor 2, which recognizes the S1P produced by damaged/apoptotic cells; after homing to the damaged site, Muse cells replace damaged/apoptotic cells by spontaneous differentiation into the damaged/apoptotic cell-type, and contribute to tissue repair, as shown by animal models of stroke, acute myocardial infarction, epidermolysis bullosa, chronic kidney disease and liver cirrhosis 14 18 . Besides their effects on tissue repair, Muse cells have pleiotropic effects including neovascularization, immunomodulation, trophic-, anti-apoptotic-, and anti-fibrotic effects 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 In addition, we reported that human Muse cells can differentiate into epidermal keratinocytes with the expression of human BMZ proteins in vivo . 9 We herein conducted a pilot study on CL2020 for the treatment of EB in human adults.…”
Section: Tablementioning
confidence: 99%
“…The labeled human SSEA-3+ Muse cells were injected intravenously through the tail vein. 35 The imaging confirmed the homing of the injected Muse cells, expressing keratin 14 and desmoglein-3 in the epidermis. Studies have shown that intravenously injected human Muse cells preferentially implant in damaged skin and spontaneously differentiate into skin components, such as keratinocytes, hair follicle cells, vascular endothelial cells and sebaceous gland cells.…”
Section: Application For Skin Ulcers In Mice Modelmentioning
confidence: 56%